A Nonlinear System of Generalized Predictive Control - Jingfang Wang (Indonesian Journal of Electrical Engineering and Computer Science, 2015)
Generalized predictive control (GPC) algorithm has been applied to all kinds of industry control systems. But systemic and effective method for nonlinear system has not been found. To this problem, this paper integrates the characteristics of PID technology and GPC, present a PID generalized predictive control algorithm for a class of nonlinear system, and improves the control quality of the system. DOI: http://dx.doi.org/10.11591/telkomnika.v13i3.7215